Pengembangan Desa Adat Gelgel sebagai Wisata Spiritual - I Made Mardika; Agus Kurniawan; Ni Komang Arini Satyawati; A. A. Ayu Dewi Larantika (Universitas Warmadewa, 2022)
Community Service on the development of the Gelgel Traditional Village as Spiritual Tourism aims to empower the community in realizing the Gelgel Traditional Village as a Spiritual Tourism Destination Area. The service partner is the Bendesa Adat Gelgel with the target audience of the Gelgel Traditional Village ‘krama’ community groups. The selection of Gelgel Traditional Village as the location of service because Gelgel has the potential to be developed into a spiritual tourism model, in accordance with the development direction of the Klungkung Regency government, and has become a guided village for the Postgraduate Program of Warmadewa University. This second year of service is programmed on the arrangement of temples and packaging of spiritual DTW icon designs as well as the preparation of Human Resources for spiritual tourism managers. The three focus partner problems that were solved were: (1) there was no physical form of